25 years of aid allocation practice: Comparing donors and eras - Paul Clist (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2009)
Focusing on seven bilateral donors over a 25 year period, the paper answers 4 questions related to aid allocation practice. Questions one and two examine allocation differences between donors and time periods. Questions three and four relate to changes in poverty and policy selectivity. To answer these questions a formal approach is used to quantify the effects of four factors that influence aid allocation: poverty, policy, proximity and population. The results reaffirm findings of large donor heterogeneity and the role of non-development influences. However, they dispute recent findings of large or growing policy sensitivity.
Keywords: F35; F50; 330; Aid Allocation; Policy Selectivity; Poverty Selectivity; Two-Part Model; Entwicklungshilfe; Entwicklungspolitik; Entwicklungsfinanzierung; Geberländer; Allokation; Armut; Entwicklungsländer